Developing a peer-based pocket book for anemia prevention in adolescent - Yahmi Ira Setyaningrum; Tabitha Sri Hartati Wulandari; Lina Listiana (JPBI (Jurnal Pendidikan Biologi Indonesia), 2026)
Background: Adolescent female anemia remains a significant health problem affecting students’ health and learning capacity, highlighting the need for innovative educational media. Objectives: This study aimed to develop and evaluate the effectiveness of a peer education–based Smart Pocket Book as a school-based intervention for anemia prevention. Methods: Using a Research and Development (R&D) approach with the ADDIE model, trained students shared and discussed pocket book content with their peers. Content validity was assessed by material and media experts, and practicality was evaluated by adolescent participants. Effectiveness was tested using a pretest–posttest control group design with 58 participants. Sample size was determined using G*Power (power = 0.80, effect size = 0.5) for group comparisons, which is generally sufficient for a school-level intervention comparing two groups using T-Test or Wilcoxon analysis. Results: The Smart Pocket Book was feasible, engaging, and easy to understand, leading to significant improvements in knowledge, attitudes, and anemia preventive behaviors (p < 0.05) and contributing to increased hemoglobin levels. Conclusion: Peer-supported use of the Smart Pocket Book is an effective school health education strategy to prevent anemia among adolescent girls.